Experiences and preliminary results on the new strategy of English language for higher education in Oriente University - Pura de la Caridad Rey Rivas; Yaritza Tardo Fernández; Fernando Casals Pierre; Ildis Houelly Pérez (Centro Provincial de Información de Ciencias Médicas, 2017)
This work has the purpose of evaluating the implementation of the new strategy of English language in  higher education from its exemplification in the  Languages Center of Oriente University, what allows to value the achieved experiences, starting from a novel training dynamics centered in a more leading and committed participation of the university students.  Some essential theoretical-methodological conceptions were taken into account that allowed the successful projection of the teaching-learning process with a vision of the present time, based on the European Common Frame of Reference for Languages. Also, the hermeneutic-dialectical approach was present in this proposal that has allowed to sustain the logic developed from the transit of observation, understanding, explanation, up to interpretation.